2006
DOI: 10.1001/archinte.166.16.1689
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Duration and Health in Young Adults

Abstract: Our data suggest that short sleep may be more of a concern than long sleep in young adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

28
245
8
5

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 358 publications
(286 citation statements)
references
References 28 publications
28
245
8
5
Order By: Relevance
“…Short sleep was also associated with being single and long working hours, whilst long sleep was also associated with low physical activity levels, pregnancy and ethnicity. These findings extend on smaller scale and less comprehensive community based studies (Mallon et al, 2002, Heslop et al, 2003, Adams, 2006, Gottlieb et al, 2006, Patel et al, 2006a, Patel et al, 2006b, Steptoe et al, 2006and Stranges et al, 2008 in identifying factors associated with short and long sleep.…”
Section: Introductionsupporting
confidence: 61%
“…Short sleep was also associated with being single and long working hours, whilst long sleep was also associated with low physical activity levels, pregnancy and ethnicity. These findings extend on smaller scale and less comprehensive community based studies (Mallon et al, 2002, Heslop et al, 2003, Adams, 2006, Gottlieb et al, 2006, Patel et al, 2006a, Patel et al, 2006b, Steptoe et al, 2006and Stranges et al, 2008 in identifying factors associated with short and long sleep.…”
Section: Introductionsupporting
confidence: 61%
“…Typically, optimal sleep duration (7-8 hr per night; Ferrara & DeGennaro, 2001) is reported among individuals with high levels of income, education, and occupational status (Krueger & Friedman, 2009;Stranges et al, 2008). This coincides with the Yerkes-Dodson principle (U-shaped pattern) that those with optimal sleep duration (neither too short nor too long) have decreased susceptibility to adverse health consequences (Ayas et al, 2004;Spiegel et al, 1999;Steptoe et al, 2006;Ursin et al, 2005). Together, these findings suggest that low subjective SEP is associated with both short (this study) and long sleep duration (Patel et al, 2006).…”
Section: Discussionmentioning
confidence: 89%
“…Inadequate sleep adversely influences multiple physiological processes important in health outcomes, including immune functioning, glucose intolerance, diabetes, metabolic syndrome, obesity, and cardiovascular disease (Ayas et al, 2004;Spiegel, Leproult & Van Cauter, 1999;Steptoe, Peacey, & Wardle, 2006).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, studies have shown that both short sleep duration, defined as sleeping ≤6 h per night, and long sleep duration, defined as sleeping ≥9 h, may be associated with many health outcomes, including total mortality (Gallicchio et al, 2009;Cappuccio et al, 2010b), cardiovascular disease (Ferrie et al, 2007;Meisinger et al, 2007;Ikehara et al, 2009;Stone et al, 2009), type 2 diabetes (Cappuccio et al, 2010a), hypertension (Guo et al, 2013), obesity (Cappuccio et al, 2008;Stranges et al, 2008a) and poor self-rated health (Steptoe et al, 2006), as well as cancers (Yang et al, 2013). Two studies reported a U-shaped association between sleep duration and cancer risk (Jiao et al, 2013;Zhang et al, 2013); whereas other studies did not reveal such an association (Kakizaki et Hao Zhao 1,2,3& , Jie-Yun Yin 2& , Wan-Shui Yang 1 , Qin Qin 2 , Ting-Ting Li 2 , Yun Shi 2 , Qin Deng 1 , Sheng Wei 2 , Li Liu 2 *, Xin Wang 1 *, Shao-Fa Nie 2 * von Ruesten et al, 2012), or only found a null association (Verkasalo et al, 2005;McElroy et al, 2006;Pinheiro et al, 2006;Sturgeon et al, 2012;Luo et al, 2013).…”
Section: Introductionmentioning
confidence: 99%